2014
DOI: 10.5603/fm.2014.0011
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the bicipital aponeurosis: a cadaveric study

Abstract: The bicipital aponeurosis (BA) is a fascial expansion which arises from the tendon of biceps brachii and dissipates (Folia Morphol 2014; 73, 1: 79-83)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Dirim et al 12 reported that the BA consists of fibers from the short and long heads of the biceps brachii muscle; in one of 17 dissected limbs, these authors observed that only the short head contributed to BA formation. Joshi et al 13 studied 30 cadaveric limbs, 16 from the right side and 14 from the left. These authors observed that the fibers that formed the distal portion of the BA originated from the short head, while those that formed the proximal portion of the BA originated from the long head of the biceps brachii muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Dirim et al 12 reported that the BA consists of fibers from the short and long heads of the biceps brachii muscle; in one of 17 dissected limbs, these authors observed that only the short head contributed to BA formation. Joshi et al 13 studied 30 cadaveric limbs, 16 from the right side and 14 from the left. These authors observed that the fibers that formed the distal portion of the BA originated from the short head, while those that formed the proximal portion of the BA originated from the long head of the biceps brachii muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we found only five anatomical studies with more than 10 cadavers. In the largest series with 50 cadavers, Joshi found an average tendon length of 7.6cm and no side difference [ 14 ]. But he did not distinguish between sex and body size, as almost all other anatomical studies [ 12 , 13 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Snoeck et al [7] measured the mean width as 0.9±0.4 cm superiorly, 1.2±0.4 cm centrally and 1.0±0.4 cm inferiorly. Joshi et al [10] dissected 30 cadaveric upper limbs (16 right, 14 left side) and measured the mean width of bicipital aponeurosis 15.74 mm on the right and 17.57 mm on the left side. In this study, the mean superior, central and inferior width of the bicipital aponeurosis were found to be 1.5±0.7 cm, 1.5±0.6 cm and 1.8±0.8 cm, respectively.…”
Section: Discussionmentioning
confidence: 99%